Carbonic anhydrase inhibitors in patients with X-linked retinoschisis: effects on macular morphology and function. (4th May 2019) - Testa, Francesco; Di Iorio, Valentina; Gallo, Beatrice; Marchese, Mario; Nesti, Anna; De Rosa, Giuseppe; Melillo, Paolo; Simonelli, Francesca
ABSTRACT: Background : Currently there is no medical treatment for X-linked retinoschisis (XLRS). In many retinal dystrophies, carbonic anhydrase inhibitors (CAIs) are effectively used to reduce cystoid macular edema. Prospective studies investigating the effect of CAIs in patients with XLRS are needed for the evaluation of their efficacy in this disease. The purpose of our work is to investigate the effects on macular morphology and function of oral CAIs used for the treatment of foveal lesions in patients with XLRS. Methods : Nineteen patients with a clinical diagnosis of XLRS were enrolled and prescribed oral CAIs for six months. We evaluated the therapeutic effect of CAIs with: best-corrected visual acuity (BCVA), spectral-domain optical coherence tomography, microperimetry (MP) and multifocal electroretinography (mfERG). Results : We observed a significant improvement of BCVA (p-value = 0.013), central retinal thickness (p-value = 0.004) and macular sensitivity (p-value<0.001). Moreover, in regards to mfERG responses, an increase of P1 wave amplitude was observed in three of the six rings. Conclusions : Our data supports the efficacy of oral CAIs for the treatment of macular cyst-like lesions in XLRS patients. The recovery of a normal retinal anatomy by means of oral CAIs could be useful to create the optimal circumstances for gene therapy. The increase in macular sensitivity and in P1 wave amplitude confirmed that MP and mfERG provide with an unbiased and more sensitive understanding of how macular function may respond to the use of CAIs. Therefore, we recommend the use of MP and mfERG to assess the effect of therapy in XLRS.